Sintesis Oksida Logam Ganda TiO2 dan Fe3O4 dalam Struktur Lapisan Bentonit Alam sebagai Material Fotokatalis - Restu Kartiko Widi (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2026)
Abstract—The synthesis of double metal oxides TiO₂ and Fe₃O₄ within the layered structure of natural bentonite as a photocatalyst material has been successfully conducted. This study aims to investigate the effect of the Ti and Fe mole ratio on the properties and structure of the resulting material. The background of this research is the successful synthesis of iron oxide in the natural bentonite layer structure without destroying the overall bentonite structure. In this research, the synthesis method used was using the sol-gel method in an inert nitrogen gas atmosphere system. The photocatalyst material was calcined using a pipe furnace at a temperature of 500 oC for 3 hours with a flow of nitrogen and oxygen gas to obtain a better metal oxide. The photocatalyst material obtained was characterized using XRD, surface analysis using N2 gas and BET and SEM-EDX methods to determine the presence and amount of Ti and Fe metal oxides formed in the bentonite layer structure. The XRD results indicate that the optimum material was obtained from the sample with a Ti : Fe mole ratio of 50 : 25 mmol, as evidenced by the presence of TiO₂ diffraction peaks in the anatase phase. In addition, the gas adsorption–desorption analysis revealed that the material exhibits mesoporous characteristics. The photocatalyst performance test was carried out on the photodegradation process of basic blue dye by providing the best removal percentage of 88% using the Bent-Ti : Fe = 50 : 25 catalyst. Keywords: photocatalyst, TiO2, Fe3O4, bentonite Abstrak—Sintesis oksida logam ganda TiO2 dan Fe3O4 dalam struktur lapisan bentonit alam sebagai material fotokatalis telah dilakukan. Penelitian ini bertujun untuk mempelajari efek rasio mol Ti dan Fe terhadap sifat dan struktur material yang dihasilkan. Latar belakang dari penelitian ini adalah keberhasilan sintesis oksida besi dalam struktur lapisan bentonit alam tanpa merusak struktur bentonit secara keseluruhan. Adapun dalam penelitian ini metode sintesis yang dilakukan adalah menggunakan metode sol-gel dalam sistem atmosfer inert gas nitrogen. Material fotokatalis dikalsinasi menggunakan tungku pipa pada suhu 500 oC selama 3 jam dengan aliran gas nitorgen dan oksigen untuk memperoleh oksida logam yang lebih baik. Material fotokatalis yang diperoleh dikarakterisasi menggunakan XRD, analis permukaan menggunakan gas N2 dan metode BET dan SEM-EDX untuk mentukan keberadaan dan jumlah oksida logam Ti dan Fe yang terbentuk dalam struktur lapisan bentonit tersebut. Dari data XRD ditunjukkan bahwa material terbaik diberikan oleh sampel dengan ratio mol Ti : Fe = 50 : 25 mmol, yang ditandai dengan munculnya puncak difraksi TiO2 fasa anatase dan kurva adsorpsi dan desorpsi gas menunjukkan material memiliki karakter mesopori. Uji keinerja fotokatalis dilakukan pada proses fotodegradasi zat warna basic blue dengan memberikan persen removal terbaik sebesar 88% menggunakan katalis Bent-Ti : Fe = 50 : 25. Kata kunci: fotokatalis, TiO2, Fe3O4, bentonit